1989
DOI: 10.3146/i0095-3679-16-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Select Peanut (Arachis hypogaea L.) Lines to Southern Stem Rot and Pythium Pod Rot Under Varied Disease Pressure

Abstract: Eight breeding lines, three parents, and the cultivar Florunner were compared under two levels of disease pressure indbced by Sclerotium rolfsii Sacc., or Pythiurn rnyriotylurn Drechs. at each of two locations for three years to ascertain the effectiveness of the host plant resistance to each pathogen. Varied disease pressures were created by application of fungicides and supplement of fungal inoculum. Mean Florunner pod yields varied more than 1000 kg/ha as a result of the S. rolfsii treatments but the yields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…Pod disease ratings for the four FlorunnerlPI 365553 runner selections averaged 1.8 compared to 1.6 for the five PI 365553!famnut 74 lines ( Table 2). The wide range in number ofloci, in both runner and spanish lines selected for Pythium pod rot resistance, concurs with our earlier observation that resistance to S. rolfsii and P. myriotylum are not a result of the same defensive mechanisms (20). The coincidental resistance to both pathogens by TxAG-3 adds attraction to its use as a parent.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Pod disease ratings for the four FlorunnerlPI 365553 runner selections averaged 1.8 compared to 1.6 for the five PI 365553!famnut 74 lines ( Table 2). The wide range in number ofloci, in both runner and spanish lines selected for Pythium pod rot resistance, concurs with our earlier observation that resistance to S. rolfsii and P. myriotylum are not a result of the same defensive mechanisms (20). The coincidental resistance to both pathogens by TxAG-3 adds attraction to its use as a parent.…”
Section: Resultssupporting
confidence: 74%
“…Partial resistance ofToalson has been reported by several researchers (6,19,20). Smith and coworkers (20) reported that resistance of TxAG-3 was considerably better than Toalson.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Although no genotypes are known to be immune or even highly resistant to S. rolfsii, several genotypes and breeding lines have been found to show lower than average susceptibility to stem rot'pod rot under field conditions (Wynne and Beute, 1983;Beute etal., 1986;Arnold etal., 1988;Smith et al, 1989;Brenneman etal., 1990;Grichar and Smith, 1992). Of several genotypes reported as partially resistant (NC 2, NC Ac 18016, NC8C, Toalson and Southern Runner), resistance of Toalson has been confirmed by several researchers (Simpson etal., 1979, Branch andCsinos, 1987;Smith etal., 1989).…”
Section: Sources Of Resistancementioning
confidence: 96%
“…Comparative reactions of certain genotypes have varied between greenhouse and field evaluations; for example NC 2 and NC Ac 18016 which showed resistance to S. rolfsii in the field were less resistant in inoculation tests in the greenhouse, while for other genotypes Garren, 1964;Beute etal., 1986;Shew et al, 1987Simpson etal., 1979Csinos, 1987 * Wynne andBeute, 1983;Beute et al, 1986;Shew et al, 1987Wynne and Beute, 1983Shew et al, 1987Arnold et al, 1988Jacob! and Backman, 1989Beute et al, 1986Brenneman etal., 1990Smith et al, 1989Grichar and Smith, 1992Grichar and Smith, 1992Branch and Brenneman, 1993 "Also resistant to pod rot caused by Pythium myriotylum and Rhizoctonia solani. b Also resistant to Cylindrocladium black rot c Also resistant to Pythium pod rot.…”
Section: Sources Of Resistancementioning
confidence: 99%